Sleep and Anesthesia - Jihyun Song; Yoo Hyun Um; Tae Won Kim; Sung Min Kim; So Young Kwon; Seung-Chul Hong (Sleep Medicine Research, 2018)
Since both anesthesia and sleep depress consciousness, bidirectional relationship between them has been further studied. Earlier findings have shown that they share electroencephalographic features and brain regions that are activated in both state of unconsciousness. Despite these similarities, medication-induced sedation provokes different outcome from natural sleep. Enlisting commonly used analgesic drugs, such as benzodiazepines, intravenous agents, benzodiazepine antagonists, opioids, and other adjuvants, the study is comprised of assorted case studies that are clinically applicable or comparable. Acknowledging potential of analgesic drugs on sleep disorders including sleep deprivation, narcolepsy, circadian rhythm disorder, periodic limb movement disorder, and obstructive sleep apnea, the study underscores the clinical importance of studying both fields, sleep and anesthesia. In conclusion, the aim of this review is explaining the consequences of analgesic agents or sedatives on sleep and sleep disorders.